Molecular Mechanisms of Acute Oxygen Sensing by Arterial Chemoreceptor Cells. Role of Hif2α - Ortega-Sáenz, Patricia; Moreno-Domínguez, Alejandro; Gao, Lin; López-Barneo, José (Frontiers in Physiology, 2020)
Carotid body glomus cells are multimodal arterial chemoreceptors able to sense and integrate changes in several physical and chemical parameters in the blood. These cells are also essential for O2 homeostasis. Glomus cells are prototypical peripheral O2 sensors necessary to detect hypoxemia and to elicit rapid compensatory responses (hyperventilation and sympathetic activation). The mechanisms underlying acute O2 sensing by glomus cells have been elusive. Using a combination of mouse genetics and single-cell optical and electrophysiological techniques, it has recently been shown that activation of glomus cells by hypoxia relies on the generation of mitochondrial signals (NADH and reactive oxygen species) which modulate membrane ion channels to induce depolarization, Ca2+ influx and transmitter release. The special sensitivity of glomus cell mitochondria to changes in O2 tension is due to Hif2-dependent expression of several atypical mitochondrial subunits, which are responsible for an accelerated oxidative metabolism and the strict dependence of mitochondrial complex IV activity on O2 availability. A mitochondrial-to-membrane signaling model of acute O2 sensing has been proposed which explains existing data and provides a solid foundation for future experimental tests. This model has also unraveled new molecular targets for pharmacological modulation of carotid body activity potentially relevant in the treatment of highly prevalent medical conditions.